Collaborative Governance Practices in Efforts to Increase Village Government Capacity to Develop Kongkil Art - Yusuf Adam Hilman; Khoirurrosyidin; Robby Darwis Nasution; Tirta Nyssa Salsabila (Indonesian Journal of Advanced Social Works, 2023)
The village administration currently has a strategic position in the practice of development and community empowerment, financial excellence is also an important factor in supporting these activities, however, creativity and innovation are also important things that must be done by the village government to develop the potential and advantages of the area they have. , so that it can become a strong and competitive village. Apart from this, villages are currently required to collaborate with other parties outside the government, so that they can support each other. This collaboration model can be developed for various activities. From this activity, it is hoped that good ideas can be used as triggers. development in the village. The conditions in Bungkal Village, Bungkal District, Ponorogo Regency have a very unique and interesting cultural wealth to develop, so that it can continue to be preserved, it is hoped that this Collaborative Governance model can be a way to develop the arts, so that villages become trained accustomed to carrying out various measurable development programs. This collaborative model can be implemented between the village government and academics, as well as artisans and kongkil artists, so that concrete steps can be taken for its existence and existence.